Kebangkitan Dan Kemunduran Umat Islam: Studi Historis Era Kepemimpinan Shalahuddin Al-Ayyubi - Ruli Jafrullah Jafrullah; Apri Wardana Ritonga; Ayat Nuraini; Andri Setiadi (Al Irsyad, 2023)
The aim of the research is to explain and describe the rise and decline of Muslims. Research was carried out in the literature where data sources came from articles, books, magazines and news. The results of this research illustrate that the era of Saladin Al-Ayyubi's leadership brought Islam towards a true revival in educational, thought, social, economic, and political aspects. Islam plays a crucial role in the nation's path. However, it turns out that Islam also has its own pluralism in the characteristics of its teachings, people, and beliefs. In the 19th century AD, the latest thinking in Islam emerged among Muslim thinkers who paid attention to the revival of Islam after experiencing a period of decline in all fields after the fall of the Abbasid Caliphate in Baghdad in 1258 AD. The impact of Hulagu's attack destroyed the buildings of Islamic civilization. At that time it was a beacon of world civilization. The emergence of the latest thoughts in Islam is motivated by 2 factors, namely external factors and internal factors. This research needs to be refined with further studies in the form of analysis of Muslim unity to achieve victory through more comprehensive data sources.